Laminate, printing ink laminate using same, and package
By adding water-soluble polymers, linear polysiloxanes and silicon alkoxides with urea groups to the protective layer of the gas barrier film, the problem of deterioration of gas barrier properties and insufficient adhesion properties in the prior art for boiling and cooking food use is solved, and a significant improvement in adhesion and gas barrier properties are achieved.
Patent Information
- Application Number
- CN202380053779.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-25
- Filing Date
- 2023-11-15
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, gas barrier films tend to deteriorate gas barrier properties during the use of boiling and cooking foods, and the adhesion of the protective layer and other resin films are insufficient, resulting in poor adhesion and gas barrier properties.
A laminate in which an inorganic compound layer and a protective layer are laminated on one side of the substrate film, the protective layer includes at least a water-soluble polymer, a linear polysiloxane and a silicon alkoxide having a urea group.
The laminated body with excellent adhesion is realized, gas barrier and adhesiveness are improved, and excellent gas barrier can be maintained after high-temperature hot water treatment.
Smart Images

Figure BDA0005241356380000091 
Figure BDA0005241356380000321 
Figure BDA0005241356380000331
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate having excellent adhesiveness, and a printing ink laminate and a package using the same. Background Art
[0002] Various packaging materials are used to package a wide range of items, including food and beverages, pharmaceuticals, and daily necessities. These packaging materials require oxygen and water vapor barrier properties to prevent the contents from deteriorating. Aluminum foil, with its excellent gas barrier properties, is used as packaging for retorted foods. However, aluminum foil packaging is prone to pinhole formation, making it difficult to handle and limiting its applications.
[0003] To address these issues, films are being used in which aluminum or aluminum oxide is deposited onto thermoplastic films such as polyester films using physical vapor deposition methods such as vacuum evaporation. These films are then treated with printing inks for display purposes such as text and patterns, or laminated to other resin films, resulting in their use as packaging materials for various applications. However, for applications such as boiling and retorting foods, which require harsh environments, a protective layer is laminated on the gas barrier layer to prevent deterioration of gas barrier properties, and this protective layer is then treated with printing ink or laminated to other resin films.
[0004] As a gas barrier film for boiling or retorting foods, there is disclosed a gas barrier film in which a vapor-deposited layer composed of an inorganic oxide or an inorganic nitride and a specific resin layer are laminated on at least one surface of a plastic film (Patent Document 1).
[0005] In addition, in order to improve the alkali boiling resistance and acetic acid boiling resistance of the vapor-deposited film and suppress changes in the appearance of the aluminum vapor-deposited layer, a laminate is disclosed in which a substrate (a), a metal vapor-deposited layer (b), and a protective layer (c) are laminated in this order, wherein the protective layer (c) contains a specific dimer acid-based polyamide resin. However, the gas barrier performance is insufficient, and the adhesion with the printed layer on the protective layer and the adhesion with other resin films are also insufficient (Patent Document 2).
[0006] In order to solve this problem, a gas barrier film in which a vapor-deposited layer composed of an inorganic compound and a specific protective layer are laminated is disclosed (Patent Documents 3 to 6).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 2010-131756
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 2012-210744
[0011] Patent Document 3: Japanese Patent No. 4403796
[0012] Patent Document 4: Japanese Patent No. 5739684
[0013] Patent Document 5: Japanese Patent Application Publication No. 2019-209645
[0014] Patent Document 6: Japanese Patent No. 4200972 Summary of the Invention
[0015] Problems to be solved by the invention
[0016] All of the above patent documents relate to a laminate formed by laminating a vapor-deposited layer composed of a metal or metal oxide layer and a specific resin layer. For example, Patent Document 3 relates to a technology for suppressing the deterioration of gas barrier properties after printing by forming the following gas barrier film, wherein the gas barrier film is formed by providing a gas barrier layer obtained from an inorganic oxide on a substrate that has been plasma-treated or laminated with a base layer, and further providing a protective layer thereon, the protective layer being formed by polymerizing a silane coupling agent monomer containing at least one of an acrylate group, a methacrylate group, and a vinyl group and a monomer containing at least one of an acrylate group, a methacrylate group, a vinyl group, and a hydroxyl group. In addition, Patent Document 4 discloses a gas barrier film formed by providing a gas barrier layer obtained from a vapor-deposited film on a substrate obtained from a synthetic resin film, and further providing a protective layer thereon for the purpose of improving gas barrier properties, the protective layer being formed by curing an alkoxysilane having a free radical polymerizable group and an alkoxysilane not having a free radical polymerizable group. However, none of these patent documents considers a laminated structure in contact with the protective layer, and therefore does not provide a protective layer component suitable for processing with printing inks or laminating with other resin films. Furthermore, although Patent Documents 5 and 6 laminate a protective layer comprising a polymer compound obtained from a hydrolyzate of a metal alkoxide and a water-soluble polymer, these patent documents, despite containing specific silicon compounds, do not consider the bonding state required to stably achieve good adhesion and gas barrier properties. Furthermore, they do not include linear polysiloxanes. Consequently, there is a problem of insufficient adhesion between the protective layer and other adjacent layers (printing ink layer, adhesive layer, resin layer, etc.), resulting in poor adhesion and poor gas barrier properties.
[0017] In view of this problem, an object of the present invention is to stably provide a laminate having excellent adhesion and a package using the same by finding an ideal state of the laminate.
[0018] Means for solving problems
[0019] The laminate of the present invention is a laminate in which an inorganic compound layer and a protective layer are laminated on at least one side of a base film, and the protective layer contains at least a water-soluble polymer, a linear polysiloxane, and a silicon alkoxide having a urea group.
[0020] Furthermore, in the laminate described above, the solid content ratio of the silicon alkoxide having a urea group relative to the total solid content of the protective layer is 2.5% or more.
[0021] In addition, regarding the laminate described in any of the above items, the protective layer further contains a silicon alkoxide without a urea group, and the mass ratio of the linear polysiloxane and the total silicon alkoxide contained in the protective layer, calculated as SiO2, is in the range of linear polysiloxane / total silicon alkoxide = 15 / 85 to 90 / 10.
[0022] In any of the above-described laminates, the water-soluble polymer contained in the protective layer is a vinyl polymer having a carbonyl group in a cyclic structure.
[0023] In any of the above-described laminates, the protective layer has an average thickness of 100 to 1000 nm.
[0024] In any of the above-described laminates, the inorganic compound layer contains aluminum oxide.
[0025] The present invention is also a printed ink laminate in which a printing ink is laminated on the protective layer side of any of the laminates described above.
[0026] The present invention also provides a package comprising any of the above-described laminates and / or a printed ink laminate in which a printing ink is laminated on the protective layer side of any of the above-described laminates.
[0027] Effects of the Invention
[0028] According to the present invention, a laminate having excellent adhesiveness and a package using the same can be provided. DETAILED DESCRIPTION
[0029] Hereinafter, the laminated body of the present invention will be described in further detail.
[0030] The laminate of the present invention is a laminate comprising an inorganic compound layer and a protective layer laminated on at least one side of a base film, wherein the protective layer comprises at least a water-soluble polymer, a linear polysiloxane, and a silicon alkoxide having a urea group.
[0031] [Base film]
[0032] The resin constituting the substrate film of the present invention is not particularly limited. Examples thereof include polyester resins such as polyethylene terephthalate, polyethylene-2,6-naphthalate, polytrimethylene terephthalate, and polybutylene terephthalate; polyolefin resins such as polyethylene, polystyrene, polypropylene, polyisobutylene, polybutene, and polymethylpentene; cyclic polyolefin resins; polyamide resins; polyimide resins; polyether resins; polyesteramide resins; polyetherester resins; acrylic resins; polyurethane resins; polycarbonate resins; and polyvinyl chloride resins. Furthermore, biodegradable resins such as polylactic acid, polycaprolactone, polyglycolic acid, and polyvinyl alcohol are also included. Among these, polypropylene is preferred from the perspective of ease of recycling. Furthermore, polyester is preferred from the perspective of recyclability, adhesion to the inorganic layer, and handleability. The resin preferably contains 3 to 55% by mass of recycled raw materials relative to the total weight of these resins. It should be noted that the recycled raw materials may be raw materials recycled through mechanical recycling or raw materials recycled through chemical recycling, and are not particularly limited. Furthermore, the resin constituting the substrate film may contain a raw material derived from biomass (derived from plants) and be a mixed resin with a raw material derived from chemical fuels. For example, in the case of polyester, it is preferred that either or both of the diol or dicarboxylic acid used as the raw material contain 10 to 95% by mass of the raw material derived from biomass (derived from plants) relative to the total resin composition.
[0033] The substrate film may be unstretched or stretched (uniaxially or biaxially), but is preferably a biaxially stretched film from the viewpoint of thermal dimensional stability.
[0034] The thickness of the substrate film is not particularly limited, but is preferably 1 μm to 100 μm, more preferably 5 μm to 50 μm, and even more preferably 10 μm to 30 μm.
[0035] In order to improve the adhesion with the inorganic layer, the surface of the base film may be subjected to corona treatment, ozone treatment, plasma treatment, glow discharge treatment, or the like, as needed.
[0036] [Inorganic compound layer]
[0037] The inorganic compound layer of the present invention is a layer containing an inorganic compound. As long as it contains an inorganic compound, it can be a mixture with an inorganic monomer. Examples of inorganic compounds include aluminum, magnesium, titanium, tin, indium, silicon, zinc, and their oxides. These can be used alone or in a mixture of two or more. The inorganic compound layer more preferably contains an inorganic compound of a metal oxide or a metal nitride. When the inorganic compound layer contains a metal oxide or a metal nitride, the durability against heat during boiling and retorting treatments, and the acid resistance against acidic contents when the laminate of the present invention is made into a package and its contents are acidic, are improved, and therefore, are preferred. Examples of metal oxides include aluminum oxide, magnesium oxide, titanium oxide, tin oxide, indium oxide alloys, silicon oxide, and silicon nitride oxide. Examples of metal nitrides include aluminum nitride, titanium nitride, and silicon nitride. These inorganic compounds can be used alone or in a mixture of two or more. In addition, the elemental composition in the inorganic layer can also be different in the thickness direction. By varying the elemental composition of the inorganic compound layer across the thickness, the adhesion between the inorganic compound layer and the protective layer can be improved, and when a laminate is formed, the inorganic compound layer and the protective layer are less likely to delaminate. Among these, oxygen and aluminum are preferred elements for the inorganic compound layer from the perspectives of production costs, gas barrier properties, heat resistance to heat during the boiling and retorting treatments, and acid resistance to acidic contents.
[0038] The method for forming the inorganic compound layer is not particularly limited. It can be formed by known methods such as evaporation, sputtering, ion plating, and plasma vapor phase growth. However, from the perspective of productivity, vacuum evaporation is preferred. In addition, as an example of a method for forming the elemental composition in the inorganic compound layer in a different manner in the thickness direction, a method for forming an inorganic compound layer in which the composition is continuously changed from an aluminum metal layer to an aluminum oxide layer is described. In this case, as a method for forming the inorganic compound layer, a method in which the composition is continuously changed from an aluminum metal layer to an aluminum oxide layer in a vacuum tank is preferably used. The method for forming the inorganic compound layer can be performed by known methods such as evaporation, sputtering, ion plating, and plasma vapor phase growth. From the perspective of productivity, evaporation is preferred. It will be described in detail. A roll-shaped substrate film is set in a vacuum tank, the substrate film is unwound, and aluminum is heated and evaporated. As a method for heating and evaporating aluminum, methods such as resistance heating, high-frequency heating, and electron beam heating can be applied. The heated evaporated aluminum adheres to the substrate film to form an aluminum metal layer. After forming the aluminum metal layer, oxygen gas is introduced during the latter half of the vapor deposition process. The introduced oxygen gas diffuses from the winding side of the substrate film to the unwinding side. This allows the oxygen reaction to proceed continuously from the aluminum metal layer to the aluminum oxide layer, resulting in an inorganic compound layer with a gradient structure whose composition continuously changes across the film thickness.
[0039] In addition, the gradient structure of the inorganic layer can be controlled by adjusting and changing the amount of oxygen when introducing oxygen, the introduction speed, the position, shape, number of introduction ports such as oxygen nozzles, the conveying speed of the substrate film, etc., but is not particularly limited to this.
[0040] As a method for measuring the film thickness in the gradient structure, X-ray photoelectron spectroscopy (XPS) is used to perform composition analysis and evaluation in the depth direction, and the film composition of the inorganic compound is confirmed by depth distribution. It should be noted that for metal elements, the components of the oxide component and the metal component are separated and distributed in a curve. While ion etching is performed from the surface layer on the protective layer side, data is collected until the substrate is reached, and the composition is confirmed to have a continuous increase or decrease based on the depth distribution of each element obtained. It should be noted that, with regard to whether there is a continuous increase or decrease, when the length of the increase or decrease is more than 2nm, it is judged to have a continuous increase or decrease.
[0041] Next, the total thickness of the inorganic compound layer is determined by the method described below. The film thickness in the gradient structure is calculated based on the total thickness of the inorganic compound layer and the region corresponding to the inorganic compound layer in the depth distribution.
[0042] The thickness of the inorganic compound layer of the present invention is preferably from 5 nm to 150 nm, and more preferably from 7 nm to 100 nm for gas barrier properties, ease of avoiding cohesive failure within the inorganic compound layer (described later), and ease of achieving adhesion. If the thickness of the inorganic compound layer is less than 5 nm, the gas barrier properties may be insufficient. On the other hand, if the thickness is greater than 150 nm, the cohesive force of the inorganic compound layer may decrease, causing cohesive failure within the inorganic compound layer, resulting in cracking or delamination of the inorganic compound layer.
[0043] [Protective layer]
[0044] The protective layer referred to in the present invention is a layer comprising at least a water-soluble polymer, a linear polysiloxane, and a silicon alkoxide having urea groups. The inclusion of a water-soluble polymer, a linear polysiloxane, and a silicon alkoxide having urea groups in the protective layer improves the adhesion between the protective layer and other adjacent layers (printing ink layer, adhesive layer, resin layer, etc.), resulting in a laminate with excellent adhesion and gas barrier properties. It is speculated that the inclusion of a water-soluble polymer and a linear polysiloxane in the protective layer densely entangles the molecular chains, forming a network of molecular chains that is fixed within the protective layer. This inhibits the movement of the molecular chains of the components constituting the protective layer and limits the paths through which gas molecules such as oxygen and water vapor can pass. Furthermore, it is speculated that the inclusion of a silicon alkoxide containing urea groups not only allows the protective layer to interact with functional groups contained in adjacent layers (printing ink layer, adhesive layer, resin layer, etc.), but also allows the protective layer to be bonded and assembled within the network of molecular chains based on the aforementioned water-soluble polymer and linear polysiloxane. This allows the components to be retained and not detached when a peeling force is applied, thereby improving adhesion. As a result, it is speculated that not only is adhesion improved, but gas barrier properties are also enhanced. In particular, the protective layer has a dense structure that can suppress the expansion of the permeation path of oxygen and water vapor gas molecules caused by environmental changes such as temperature, thereby exhibiting excellent gas barrier properties even after high-temperature hot water treatment such as boiling or retorting.
[0045] As the water-soluble polymer in the present invention, for example, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, modified polyvinyl alcohol, etc. can be mentioned. These polymers can be used alone or in the form of a mixture of two or more, but vinyl alcohol-based polymers (including modified polyvinyl alcohol) are preferred. Vinyl alcohol-based polymers (including modified polyvinyl alcohol) are usually obtained by saponifying polyvinyl acetate. They can be partially saponified by saponifying a part of the acetic acid group, or they can be completely saponified, but vinyl alcohol-based polymers with a high degree of saponification are preferred. The degree of saponification is preferably 90% or more, more preferably 95% or more. If a large number of acetic acid groups with a low degree of saponification and large steric hindrance are contained, the free volume of the protective layer sometimes becomes larger. The degree of polymerization of the vinyl alcohol-based resin is preferably 1,000 to 3,000, more preferably 1,000 to 2,000. When the degree of polymerization is low, the polymer is difficult to fix, and sometimes it is difficult to exhibit adhesion and gas barrier properties.
[0046] Furthermore, as a particularly preferred water-soluble polymer, a vinyl polymer having a carbonyl group in a cyclic structure. By including a vinyl polymer having a carbonyl group in a cyclic structure as a water-soluble polymer in the protective layer, it is believed that the hydrophobization based on the cyclic structure and the interaction around the polymer based on the carbonyl group form a dense structure film, which improves water resistance and forms a protective layer with a dense structure with low hydrophilicity, reducing the interaction with gas molecules such as oxygen and water vapor, blocking the permeation path of gas molecules, thereby showing excellent gas barrier properties while showing close adhesion. It should be noted that the vinyl polymer having a carbonyl group in the cyclic structure of the present invention is preferably 20 to 100% by mass in the total water-soluble polymer 100% by mass in the protective layer. If the content of the vinyl polymer having a carbonyl group in the cyclic structure is less than 20% by mass, the effect of improving the gas barrier properties is sometimes insufficient. The most preferred content is that all water-soluble polymers are vinyl polymers having a carbonyl group in the cyclic structure, i.e., 100% by mass.
[0047] As a cyclic structure, as long as it is a three-membered ring or more (for example, a three- to six-membered ring), there is no particular limitation. In addition, it can be a cyclic structure such as a heterocyclic ring having heteroelements such as nitrogen, oxygen, sulfur, phosphorus, etc. other than carbon in the cyclic structure. In addition, the site with a carbonyl group in the cyclic structure can be present in any site of the main chain, side chain, or cross-linked chain in the vinyl polymer. As these vinyl polymers having a carbonyl group in the cyclic structure, specifically, for example, lactone structures as cyclic esters and lactam structures as cyclic amides can be mentioned. These can be used alone or include two or more types. There is no particular limitation, but lactone structures are preferred. If a vinyl polymer with a lactone structure is used as a water-soluble polymer, it is stable with respect to the acid catalyst used for the hydrolysis of the silicon alkoxide described later, and it is easy to maintain gas barrier properties. As vinyl polymers with a lactone structure, for example, α-acetone lactone, β-propiolactone, γ-butyrolactone, δ-valerolactone, etc. can be mentioned.
[0048] Regarding the linear polysiloxane in the present invention, since there are few pores in the molecular chain, the molecular chains can exist at a high density with each other, so it is presumed that a network of molecular chains is formed and fixed in the protective layer, thereby being able to suppress the movement of the molecular chains of the components constituting the protective layer, thereby forming a protective layer with a dense structure, and improving the adhesion and gas barrier properties. The linear polysiloxane is a substance represented by the following chemical formula (1), wherein n in the chemical formula (1) is an integer greater than 2. Regarding R in the chemical formula (1), as a lower alkyl group, for example, methyl, ethyl, n-propyl, and n-butyl can be mentioned, and as a branched alkyl group, isopropyl, tert-butyl, etc. can be mentioned. In the present invention, if the linear structure of the linear polysiloxane is longer, it is easy to form a network and fix it in the protective layer, so n is preferably 5 or more, and more preferably 10 or more.
[0049] [Chemical Formula 1]
[0050]
[0051] Linear polysiloxanes can be obtained from silicon alkoxides represented by Si(OR)4. R in silicon alkoxides is preferably a lower alkyl group, for example, methyl, ethyl, n-propyl, and n-butyl. As silicon alkoxides, specifically, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane can be mentioned, which can be used alone or in the form of a mixture of two or more. Silicon alkoxides can be hydrolyzed, for example, to obtain linear polysiloxanes. Silicon alkoxides are hydrolyzed in the presence of Si(OR)4, water, a catalyst, and an organic solvent. The amount of water used for hydrolysis is preferably 0.8 equivalents to 5 equivalents, more preferably 1.0 equivalents to 4 equivalents, relative to the alkoxy group of Si(OR)4. If the amount of water is less than 0.8 equivalents, the hydrolysis cannot be fully carried out, and sometimes linear polysiloxanes cannot be obtained. When the amount of water exceeds 5 equivalents, the reaction of the silicon alkoxide described later proceeds randomly, and a large amount of non-linear polysiloxane is formed, and linear polysiloxane may not be obtained.
[0052] The catalyst for hydrolysis is preferably an acid catalyst. Examples of acid catalysts include hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, tartaric acid, etc., which are not particularly limited. Generally, the hydrolysis and polycondensation reaction of silicon alkoxide can be carried out with an acid catalyst or a base catalyst. However, when an acid catalyst is used, the monomers in the system are easily hydrolyzed evenly and easily become straight-chain. On the other hand, when a base catalyst is used, since the reaction mechanism is that the alkoxide bonded to the same molecule easily undergoes hydrolysis and polycondensation, the reaction proceeds randomly and the reaction product easily becomes a state with many gaps. The amount of the catalyst used is preferably 0.1 mol % or more and 0.5 mol % or less relative to the total molar amount of silicon alkoxide.
[0053] As the organic solvent used for the hydrolysis, alcohols such as methanol, ethanol, n-propanol, isopropanol, and n-butanol that are miscible with water and silicon alkoxide can be used.
[0054] The hydrolysis temperature is preferably 20°C to 45°C. When the reaction is carried out at a hydrolysis temperature below 20°C, the reactivity is low, and the hydrolysis of Si(OR)4 may be difficult to proceed. On the other hand, when the reaction is carried out at a temperature above 45°C, the hydrolysis and polycondensation reactions proceed rapidly, and gelation may occur, or a non-linear, random, and sparse polysiloxane may be formed.
[0055] The silicon alkoxide having a urea group in the present invention may be a silicon alkoxide having urea groups in its structure, and may be a silicon alkoxide having 1 to 3 functional groups. The urea groups may be bonded to the silicon atoms in the silicon alkoxide via linear or branched alkyl chains such as methyl, ethyl, or propyl groups. One type or a mixture of two or more types may be used, taking into account the required properties, productivity, etc. Examples of the silicon alkoxide having a urea group include KBM-585 and KBM-585A manufactured by Shin-Etsu Chemical Co., Ltd., A-1160 manufactured by Momentive Performance Materials Japan, and "DOWSIL" (registered trademark) Z-6119 Silan, "DOWSIL" Z-6120 Silan, and "DOWSIL" Z-6675 Silan manufactured by Dow Toray Industries, Ltd. Commercially available products from various manufacturers may be used.
[0056] The protective layer of the present invention may further contain a silicon alkoxide without a urea group in addition to a water-soluble resin, a linear polysiloxane, and a silicon alkoxide having a urea group. The silicon alkoxide without a urea group may be the aforementioned silicon alkoxide represented by Si(OR)4, a silicon alkoxide having a functional group such as a silane coupling agent, and is not particularly limited as long as it does not hinder the effects of the present invention.
[0057] [Composition of protective layer]
[0058] In the present invention, the solid content ratio of the silicon alkoxide with a urea group relative to the total solid content in the protective layer is preferably 2.5% or more. If the solid content ratio of the silicon alkoxide with a urea group is 2.5% or more, it is easy to bond and entangle in the network of molecular chains based on water-soluble polymers and linear polysiloxanes, and the components are easily retained and not detached during peeling, making it easier to show adhesion. The solid content ratio of the silicon alkoxide with a urea group is preferably 5.0% or more, and more preferably 8.0% or more. In addition, the upper limit of the solid content ratio of the silicon alkoxide with a urea group is not particularly limited, but when it is higher than 50%, the water-soluble polymers and linear polysiloxanes in the protective layer become less, the network of molecular chains becomes sparse, and the gas barrier properties are sometimes reduced. Therefore, it is preferably 50% or less. It should be noted that the solid content ratio of the silicon alkoxide with a urea group can be measured by the method described below.
[0059] In the present invention, it is preferred that the total content of all water-soluble resins in the protective layer is 20 to 80% by mass in 100% by mass of the protective layer. If the content of the water-soluble resin is 20 to 80% by mass, it is easy to form a protective layer with a dense structure, and it is easy to exhibit excellent gas barrier properties while showing close adhesion. If the content of the water-soluble resin is less than 20% by mass, the protective layer tends to harden, sometimes cracking and reducing gas barrier properties. If the content of the water-soluble resin is greater than 80% by mass, the water-soluble resin cannot be fixed, and sometimes the gas barrier properties are reduced. The content of the water-soluble resin is more preferably 25 to 60% by mass, and even more preferably 30 to 50% by mass.
[0060] In the present invention, the total content of all linear polysiloxanes in the protective layer can be 20 to 80% by mass based on 100% by mass of the protective layer. As described above, silicon alkoxides (including hydrolyzates of silicon alkoxides) with or without urea groups may be further included. Therefore, regarding the content, the total content of the inorganic components in the protective layer (hereinafter referred to as "protective layer inorganic components") is preferably 20 to 80% by mass, more preferably 30 to 65% by mass, based on SiO2 conversion of the linear polysiloxanes and the total silicon alkoxides. It should be noted that the contents of the water-soluble resin and the protective layer inorganic components in the protective layer can be measured by the method described below.
[0061] In the present invention, the mixing ratio of the linear polysiloxane and the total silicon alkoxide in the protective layer can be adjusted. The mixing ratio is preferably such that the mass ratio of the linear polysiloxane and the total silicon alkoxide converted by SiO2 is within the range of linear polysiloxane / total silicon alkoxide = 15 / 85 to 90 / 10, more preferably within the range of 40 / 60 to 85 / 15, and further preferably within the range of 40 / 60 to 65 / 35. When this value exceeds 90 / 10, the interaction between the linear polysiloxanes becomes stronger, and the above-mentioned water-soluble resin and the silicon alkoxide with urea group cannot be fixed, and sometimes the adhesion and gas barrier properties are reduced. On the other hand, if this value is less than 15 / 85, the Si-OH bonds derived from the silicon alkoxide become more, thereby increasing the hydrophilicity and sometimes reducing the gas barrier properties. The mixing ratio of the linear polysiloxane and the silicon alkoxide in the protective layer can be measured by the method described below.
[0062] It should be noted that, by using an oligomer raw material to which a plurality of Si(OR)4 are pre-bonded as a linear polysiloxane, the mixing ratio of the linear polysiloxane and the silicon alkoxide can be easily adjusted. Examples of the oligomer raw material to which a plurality of Si(OR)4 are pre-bonded include linear oligomers in which alkyl silicates are polymers, such as methyl silicate in which R is a methyl group and ethyl silicate in which R is an ethyl group in the chemical formula (1).
[0063] In the present invention, the linear polysiloxane and each silicon alkoxide contained in the protective layer can be subjected to a polycondensation reaction using heat to form a protective layer. During the polycondensation reaction, the alkoxy group and / or hydroxyl group contained in the linear polysiloxane and each silicon alkoxide is reduced, forming a protective layer with a dense and tough structure. In addition, through the polycondensation reaction, the molecular weight of the linear polysiloxane and each silicon alkoxide becomes larger, and thus the ability to fix the water-soluble resin and the silicon alkoxide having a urea group itself becomes higher. Therefore, the protective layer can improve the adhesion and gas barrier properties by reacting with heat, so a higher temperature is preferred. However, when the temperature is higher than 200°C, the base film sometimes shrinks due to heat, or strain and cracks are generated in the inorganic compound layer, thereby reducing the gas barrier properties.
[0064] The protective layer can be obtained by applying a coating solution containing protective layer components (hereinafter referred to as the protective layer coating solution) onto the inorganic compound layer and drying it. Therefore, the temperature for the polycondensation reaction, i.e., the drying temperature of the coating film, is preferably from 100°C to 200°C, more preferably from 120°C to 180°C, and even more preferably from 150°C to 180°C. If the drying temperature is lower than 100°C, water contained as a solvent (described later) may not evaporate sufficiently, and the layer may not solidify.
[0065] The protective layer coating solution can be obtained by mixing a solution of a water-soluble resin dissolved in water or a water / alcohol mixed solvent with a solution containing a linear polysiloxane and a silicon alkoxide with or without a urea group. Examples of alcohols used in the solvent include methanol, ethanol, n-propanol, isopropanol, and n-butanol.
[0066] As a method for applying the protective layer coating liquid onto the inorganic compound layer, known methods such as direct gravure, reverse gravure, micro gravure, rod coating, bar coating, die coating, and spray coating can be used without particular limitation.
[0067] The protective layer according to the present invention may contain a leveling agent, a crosslinking agent, a curing agent, an adhesion agent, a stabilizer, an ultraviolet absorber, an antistatic agent, etc., as long as the adhesion and gas barrier properties are not impaired. Examples of crosslinking agents include metal alkoxides of aluminum, titanium, zirconium, and the like, and their complexes.
[0068] The average thickness of the protective layer is preferably from 10 nm to 1,000 nm, more preferably from 100 nm to 600 nm, and even more preferably from 250 nm to 500 nm. If the average thickness is less than 10 nm, pinholes and cracks in the inorganic compound layer may not be adequately filled, and sufficient gas barrier properties may not be achieved. On the other hand, if the thickness exceeds 1,000 nm, cracks may form due to the thickness.
[0069] As mentioned above, the protective layer utilizes heat to cause the condensation reaction to proceed, thereby improving the gas barrier properties. Therefore, it is also preferred to further heat-treat the laminate after forming the protective layer in order to improve the gas barrier properties. The heat treatment temperature is preferably from 30°C to 100°C, more preferably from 40°C to 80°C. The heat treatment time is preferably from 1 day to 14 days, more preferably from 3 days to 7 days. When the heat treatment temperature is lower than 30°C, the thermal energy required to promote the reaction is insufficient, and the effect is sometimes small; when it is higher than 100°C, curling of the substrate sometimes occurs, oligomers are generated, and the cost of equipment and manufacturing becomes high.
[0070] [Analysis of Laminated Body]
[0071] The presence of linear polysiloxane in the protective layer of the present invention can be confirmed by laser Raman spectroscopy. Regarding laser Raman spectroscopy, as the bonding state of linear polysiloxane and metal alkoxide (including hydrolyzates of metal alkoxide), the Raman bands of linear polysiloxane, random network structures containing ring structures of five or more members and branches, and four-membered ring structures can be detected at 400 to 500 cm -1 Since these Raman bands overlap, the -1 A four-membered ring structure was observed at 488 cm -1 The linear polysiloxane was observed, and the random network structure was not a single regular structure, so at 450 cm -1 The following spectrum has broad peaks, which can be fitted by Gaussian function approximation for peak separation.
[0072] A method for determining the content of water-soluble resin and inorganic components (straight-chain polysiloxane, total silicon alkoxide (including hydrolyzates of silicon alkoxide)) in the protective layer is described. As described above, the amount of straight-chain polysiloxane and total silicon alkoxide (including hydrolyzates of silicon alkoxide) as inorganic components can be converted into silicon content, and the total silicon content can be obtained by fluorescent X-ray analysis. First, five standard samples with known and different total silicon contents are prepared, and fluorescent X-ray analysis is performed on each sample. In fluorescent X-ray analysis, X-ray irradiation is used to generate and detect inherent fluorescent X-rays of elements. The amount of X-rays generated is proportional to the amount of the element contained in the measurement object, so the X-ray intensity S (unit: cps / μA) of silicon obtained by measurement is proportional to the total silicon content. Here, the thickness of the standard sample is calculated using the same method as the average thickness T described later. The X-ray intensity S obtained by fluorescent X-ray analysis is divided by the thickness of the standard sample to calculate the X-ray intensity S per unit thickness. The known total silicon content and the X-ray intensity S per unit thickness are plotted to create a calibration curve. Then, in the laminate of the present invention, the X-ray intensity S per unit thickness is similarly calculated based on the fluorescent X-ray analysis and the average thickness T, and the total silicon content is calculated using the calibration curve and this value. Based on this total silicon content, the total molar number of total silicon atoms contained in the linear polysiloxane and total silicon alkoxide is calculated and converted into SiO2 mass. From this, the total mass ratio S of the inorganic components of the protective layer is calculated, and the content ratios of the water-soluble resin and various inorganic components can be determined.
[0073] Regarding the mixing ratio of straight-chain polysiloxane and silicon alkoxide in the inorganic components in the protective layer, the ratio of the area A1 of the Raman band representing the random network structure to the area A2 of the Raman band representing the straight-chain polysiloxane obtained by the above-mentioned laser Raman spectroscopy, that is, A2 / A1, becomes the mixing ratio of straight-chain polysiloxane / total silicon alkoxide (mass ratio converted into SiO2).
[0074] Furthermore, the mixing ratio of the water-soluble resin and the linear polysiloxane / total siliconate (mass ratio based on SiO2 conversion) is determined using the above method. Five standard samples are then prepared, each with a known and varying ratio of the solid content of siliconate with urea groups within the solid content of the siliconate in this composition. Fluorescence X-ray analysis is performed on each sample in the same manner as described above, and the amount of X-rays generated is measured. Here, the X-ray intensity S (unit: cps / μA) of silicon varies depending on the solid content ratio of siliconate with urea groups. Similarly, the thickness of the standard samples is calculated using the same method as the average thickness T described below. A calibration curve is created by plotting the known solid content ratio of siliconate with urea groups against the X-ray intensity S per unit thickness. Then, for the laminate of the present invention, the X-ray intensity S per unit thickness is similarly determined using the fluorescence X-ray analysis and the average thickness T. Based on the calibration curve and its value, the X-ray intensity S is converted to the solid content ratio of siliconate with urea groups and calculated.
[0075] [Printing ink laminate]
[0076] The printing ink laminate of the present invention is a laminate in which printing ink is laminated as a printing ink layer on the protective layer side of the laminate. It should be noted that the printing ink layer can be similarly laminated on the opposite side of the protective layer side of the laminate to make a laminate with printing ink layers laminated on both sides of the laminate. Usually, the printing ink layer is laminated for the purpose of displaying content information, light-shielding, decorativeness, design, etc., so the printing ink layer includes a colorant and a resin. As needed, optional additives can be included, for example, curing agents, lubricants, anti-blocking agents, leveling agents, defoamers, pigment dispersants, silane coupling agents, ultraviolet absorbers, rust inhibitors, plasticizers, flame retardants, reinforcing agents, antistatic agents, viscosity modifiers, etc. About colorants, there is no particular limitation, and inorganic pigments, organic pigments, dyes, etc. can be appropriately selected for use. In addition, about resin, castor oil, polyester resin, polyurethane resin, epoxy resin, (methyl) acrylic resin, melamine resin, polystyrene resin, phenolic resin, polyvinyl chloride resin, polyvinyl acetate resin, polyamide resin, nitrocellulose, acrylate compound polymer or their mixture etc. can be enumerated, but is not limited to this.And then, as the method for forming the above-mentioned printing ink layer, letterpress printing, gravure printing, offset printing, flexographic printing, screen printing etc. can be enumerated, can be arbitrarily selected.As printing ink, commercially available product can be used, and can enumerate as the reverse printing gravure ink Toyo Ink Co., Ltd. manufactures LPBIO series or LIOALPHA S series, DIC Corporation manufactures FINART S series, FINART BM series, SAKATAINX Corporation manufactures Belle Color series, Belle Flora series, Dainichi Seika Co., Ltd. manufactures LAMICSR series, LAMIC BP series, NB300BP series, Tokyo Ink Co., Ltd. manufactures LG-NT series etc.
[0077] [Packaging]
[0078] The packaging body of the present invention is formed by laminating a heat-sealable thermoplastic resin onto at least one surface of either the laminate or the printing ink laminate of the present invention via an adhesive layer such as an adhesive, and then molding the resulting package into a bag shape with the thermoplastic resin as the inner side. A resin film such as a polyester film, a polyamide film, or a polypropylene film, the laminate or printing ink laminate of the present invention, various vapor-deposited films, a functional resin film such as a polyvinylidene chloride coating film, or a thermoplastic resin may be laminated onto the other surface of the surface laminated with the thermoplastic resin, and between the laminate or printing ink laminate of the present invention and the thermoplastic resin. Examples of adhesives used in the adhesive layer include one-component or two-component curable adhesives such as vinyl, (meth)acrylic, polyamide, polyester, polyether, polyurethane, epoxy, and rubber adhesives, and include solvent-based, water-based, and emulsion-based adhesives. Examples of commercially available adhesives include two-component curable polyester adhesives such as TM-570 / CAT-RT37 manufactured by Toyo Ink Co., Ltd., LX500 / KO55 manufactured by DIC Corporation, RU-77T / H-7 manufactured by Rock Paint Co., Ltd., A-620 / A-6 manufactured by Mitsui Chemicals, Inc., A4210R / CA75 manufactured by Dainichi Seika Co., Ltd., and LA2760 / LA5891 manufactured by Henkel Corporation. Furthermore, to improve gas barrier properties, PASLIM VM001 / VM108CP manufactured by DIC Corporation can also be used.
[0079] The adhesive can be applied by any method, such as direct gravure coating, reverse roll coating, kiss coating, or spraying, without particular limitation. The amount of coating after drying is preferably 0.1 g / m 2 Above 10g / m 2 Below, more preferably 1g / m 2 More than 5g / m 2As the thermoplastic resin, polyethylene resin, polypropylene resin or cyclic polypropylene resin or copolymer resins or mixed resins with these resins as main components can be used. For example, low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), linear (linear) low-density polyethylene (LLDPE), polypropylene (PP), ethylene-α / olefin copolymers obtained by metallocene catalyst polymerization, random or block copolymers of ethylene / polypropylene, ethylene / vinyl acetate copolymer (EVA), ethylene / acrylic acid copolymer (EAA), ethylene / ethyl acrylate copolymer (EEA), ethylene / methacrylic acid copolymer (EMAA), ethylene / methyl methacrylate copolymer (EMMA), ethylene / maleic acid copolymer, ionomer resin, and acid-modified polyolefin resins obtained by modifying the above-mentioned polyolefin resins with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, etc. can be used. The packaging body of the present invention has excellent adhesion and gas barrier properties by using the laminate or printed ink laminate of the present invention, and does not cause defects such as peeling after filling with contents, and can safely store the contents. Therefore, it is possible to provide a packaging body that will not peel due to heat applied during boiling or steaming, or acid in the case where the contents are acidic substances.
[0080] [use]
[0081] The laminate of the present invention has high adhesion and gas barrier properties and can be suitably used as a package containing the laminate of the present invention.
[0082] Example
[0083] Hereinafter, the present invention will be further specifically described with reference to Examples, but the present invention is not limited to these Examples.
[0084] (1) Component Analysis and Structural Identification of the Protective Layer (Water-Soluble Resin, Linear Polysiloxane, Siliconate with Urea Group)
[0085] The protective layer is peeled off from the sample and dissolved in a soluble solvent. Next, the solution is filtered to separate the particles and the filtrate. As needed, the components contained in the protective layer and the resin layer are separated and purified into single substances using general chromatography represented by silica gel column chromatography, gel permeation chromatography, high performance liquid chromatography, etc. Then, DMSO-d6 is added to each single substance, heated to 60°C to dissolve each single substance, and the solution is subjected to nuclear magnetic resonance spectroscopy. 1 H-NMR, 13C-NMR measurement. Then, IR method (infrared spectroscopy), various mass spectrometry (gas chromatography-mass spectrometry (GC-MS), thermal decomposition gas chromatography-mass spectrometry (thermal decomposition GC-MS), matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS), time-of-flight mass spectrometry (TOF-MS), matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS), dynamic secondary ion mass spectrometry (Dynamic-SIMS), time-of-flight secondary ion mass spectrometry (TOF-SIMS) are appropriately combined to perform qualitative analysis on each single substance, and determine and identify the components contained in the sample. It should be noted that when combining these qualitative analyses, the qualitative analysis that can be measured with fewer combinations is preferably applied.
[0086] (2) Average thickness of protective layer and total thickness of inorganic compound layer
[0087] Regarding the average thickness of the protective layer and the total thickness of the inorganic compound layer, the cross section was observed using TEM. First, a micro-sampling system (FB-2000A manufactured by Hitachi, Ltd.) was used to prepare a sample for cross-sectional observation using the FIB method (specifically, based on the method described in "Polymer Surface Processing" (written by Akira Iwamori) p. 118-119). Next, a transmission electron microscope (H-9000UHRII manufactured by Hitachi, Ltd.) was used to observe at an accelerating voltage of 300 kV. The observation magnification was adjusted so that the ratio of the layer thickness in the observed image became 30-70%, and the obtained cross section was observed. A total of 5 samples were measured in the same way, and the average value of the total 5 points was calculated. The value converted to nm was used as the average thickness and the total thickness of the inorganic compound.
[0088] (3) Determination of the content ratio of water-soluble resin and inorganic component (linear polysiloxane, silicon alkoxide) in the protective layer
[0089] Prepared as standard samples with different content ratios are films containing a hydrolyzate of polyvinyl alcohol (hereinafter sometimes referred to as PVA. Degree of polymerization 1,700, degree of saponification 98.5%) as a water-soluble resin and tetraalkoxysilane (hereinafter sometimes referred to as TEOS) as an inorganic component, and mixed in such a manner that the content ratio of water-soluble resin / inorganic component (inorganic component is converted to SiO2 mass) is 80 / 20, 65 / 35, 50 / 50, 35 / 65, and 20 / 80.
[0090] Next, the intensity of silicon-specific X-rays Kα was measured for each standard sample using an EDX-700 fluorescent X-ray analyzer manufactured by Shimadzu Corporation, and the resulting X-ray intensity S (unit: cps / μA) was determined. The thickness of each standard sample was measured using the method described in (2) above, and the X-ray intensity S per unit thickness was calculated to create a calibration curve for the content of the water-soluble resin and the inorganic component (the inorganic component is converted to SiO2 mass).
[0091] Next, for the laminate of the present invention, the X-ray intensity S per unit thickness was similarly determined from the fluorescent X-ray analysis and the average thickness T, and the contents of the water-soluble resin and the inorganic component were determined from the calibration curve.
[0092] (4) Analysis of the bonding state of silicon (presence of linear polysiloxane), (mixing ratio of linear polysiloxane / silicon alkoxide (mass ratio in terms of SiO2))
[0093] The protective layer of the laminate was separated by cutting and analyzed by Raman spectroscopy under the following conditions.
[0094] Measuring device: Jobin Yvon / Atago T-6400
[0095] Measurement mode: Micro-Raman
[0096] Objective lens: 100x
[0097] Beam diameter: 1 μm
[0098] Light source: Ar + Laser / 514.5nm
[0099] Laser power: 200mW
[0100] Diffraction grating: Single 600gr / mm
[0101] Slit: 100μm
[0102] Detector: CCD / Jobin Yvon 1,024×256
[0103] The Raman spectrum analysis conditions used to calculate the area A1 representing the random network structure formed by the silicon alkoxide and the area A2 representing the linear polysiloxane are shown below. The obtained Raman spectrum was analyzed using the spectrum analysis software GRAMS / Thermo Scientific. The Raman spectrum was baseline corrected using a linear approximation and the peaks were calculated between 600 and 250 cm. -1 For the fitting, the four-membered ring structure (peak wave number 495cm -1 、Half width 35cm-1 ), linear polysiloxane (peak wave number 488cm -1 、Half width 35cm -1 ), and a random network structure formed by silicon alkoxides. The random network structure formed by silicon alkoxides is a broad peak reflecting a continuous structure, so it was separated into three components combined with the four-membered ring structure and the linear polysiloxane using Gaussian approximation and automatic fitting was performed.
[0104] The presence or absence of linear polysiloxane is determined by calculating the area of the obtained spectral band and the area surrounded by the baseline, and the area representing the random network structure formed by silicon alkoxide is set as A1, and the area representing the linear polysiloxane is set as A2, and A2 / A1 (mixing ratio of linear polysiloxane / silicon alkoxide (mass ratio converted into SiO2)) is calculated.
[0105] (5) Solid content ratio of silicon alkoxide having urea group relative to the total solid content in the protective layer
[0106] The mixing ratio of the water-soluble resin and the linear polysiloxane to the total siliconate (mass ratio in terms of SiO2) is determined by the methods (3) and (4) above. Five standard samples are then prepared, each with a known and different solid content ratio of siliconate having urea groups in the solid content of the siliconate corresponding to the composition. Fluorescent X-ray analysis of each sample is performed in the same manner as in (3) above, and the amount of X-rays generated is detected. Subsequently, a calibration curve is prepared by plotting the solid content ratio of siliconate having urea groups against the X-ray intensity S per unit thickness in the same manner as in (2) and (3) above.
[0107] Next, for the laminate of the present invention, the X-ray intensity S per unit thickness is similarly calculated based on fluorescent X-ray analysis and the average thickness T, and this value is converted into the solid content ratio of the silicon alkoxide having a urea group using the calibration curve to calculate the solid content ratio of the silicon alkoxide having a urea group.
[0108] (6) Gas barrier properties (oxygen barrier properties: oxygen permeability, water vapor barrier properties: water vapor permeability)
[0109] Prepare the laminate of the present invention. Next, regarding the oxygen permeability (hereinafter sometimes referred to as OTR), under the conditions of temperature 23°C and humidity 90% RH, an oxygen permeability measuring device ("OX-TRAN" (registered trademark) 2 / 21) manufactured by MOCON was used to measure based on JIS K7126-2 (2006). The measurement was performed twice on each of the two test pieces, and the average value of the total of four measured values was taken as the value of the oxygen permeability of the laminate in the present invention. In addition, regarding the water vapor permeability (hereinafter sometimes referred to as WVTR), under the conditions of temperature 40°C and humidity 90% RH, a water vapor permeability measuring device ("PERMATRAN" (registered trademark) -W 3 / 31) manufactured by MOCON was used to measure based on JIS K7129-2 (2019). The measurement was performed twice on each of the two test pieces, and the average value of the total of four measured values was taken as the value of the water vapor permeability of the laminate in the present invention.
[0110] Next, a laminated film for barrier evaluation was prepared by laminating a 60 μm thick unstretched polypropylene film (ZK100, manufactured by Toray Films, Ltd.) onto the protective layer side of the laminate of the present invention via an adhesive containing a polyester urethane base (LX500, manufactured by DIC Corporation) and an aliphatic isocyanate curing agent (KO55, manufactured by DIC Corporation). This laminated film for barrier evaluation was then subjected to retort sterilization (high-temperature hot water treatment) at 135°C for 30 minutes to produce a laminated film for barrier evaluation after retort treatment. Two test pieces were each measured twice using the same method as for the above-described laminate. The average of the four measured values was used as the oxygen transmission rate and water vapor transmission rate after retort treatment in the present invention.
[0111] (7) Adhesion evaluation (laminar strength of ink layer)
[0112] The adhesion evaluation of the laminate was performed by the following method.
[0113] On the protective layer side of the laminate, white printing ink (Bellecolor R White 115DT manufactured by Sakata Inks Co., Ltd.) was gravure printed in a solid state so that the printing ink thickness after drying would be 1 μm, thereby producing a printed ink laminate. Subsequently, the coating amount of the cured adhesive was set to 3 g / m 2In a manner, an adhesive comprising a polyester urethane main agent (LX500 manufactured by DIC Corporation) and an aliphatic isocyanate curing agent (KO55 manufactured by DIC) is applied to the corona treated surface of a 15 μm thick stretched nylon film (EMBLEM ONUM manufactured by UNITIKA Co., Ltd.), and the adhesive is laminated to the printed ink surface of the printed ink laminate to obtain a laminated film for evaluating the adhesion of the printed ink laminate and the stretched nylon film. Next, the laminated film for evaluating adhesion was cut into 15 mm wide and 150 mm long samples. A tensile testing machine (TENSILON) was used to measure the peel strength at a peeling speed of 50 mm / min with a peeling angle of 180 ° at the interface between the protective layer and the printed layer of the printed ink laminate. A total of three samples were measured using the above-mentioned measurement method, and the average value of the measured values was used as the value of the initial lamination strength. Furthermore, the laminated film for adhesion evaluation was subjected to a steam sterilization treatment at 135°C for 30 minutes, and cut into pieces with a width of 15 mm and a length of 150 mm to prepare cut samples. The peel strength of a total of three samples was measured using the same method as above, and the average of the measured values was taken as the lamination strength after steam sterilization.
[0114] [Example 1]
[0115] <Inorganic Compound Layer>
[0116] A 12 μm-thick biaxially stretched polyethylene terephthalate film ("Lumirror" (registered trademark) P60 manufactured by Toray Industries, Inc.) was used as the base film, and a 15 nm-thick aluminum oxide layer was formed as the inorganic compound layer by vacuum deposition.
[0117] <Protection layer>
[0118] (Organic component solution)
[0119] Polyvinyl alcohol (hereinafter also referred to as PVA, degree of polymerization 1,700, degree of saponification 98.5%) as a water-soluble resin was added to a solvent having a mass ratio of water / isopropyl alcohol = 97 / 3, and heated and stirred at 90°C to obtain an organic component solution having a solid content of 12% by mass.
[0120] (Inorganic component solution)
[0121] To a solution prepared by mixing 11.7 g of KBM-585A manufactured by Shin-Etsu Chemical Co., Ltd., a silicon alkoxide having a urea group, and 4.7 g of methanol, 18.6 g of a 0.02N aqueous hydrochloric acid solution was added dropwise with stirring to obtain a silicon alkoxide having a urea group hydrolyzed solution (hydrolyzed solution A).
[0122] Next, 7.0 g of a 0.06 N aqueous hydrochloric acid solution was added dropwise to a solution of 11.2 g of ethyl silicate 40 (linear oligomer with an average pentamer) manufactured by COLCOAT Co., Ltd., which is a linear polysiloxane, and 16.9 g of methanol to obtain a pentameric silicate hydrolyzed liquid (hydrolyzed liquid B).
[0123] (Forming a protective layer)
[0124] The organic component solution, hydrolysis solution A, and hydrolysis solution B were mixed and stirred so that the PVA content was 20% by mass, the solid content of the urea-containing siliconate was 2.0%, and the SiO2-converted mass ratio of the linear polysiloxane to the siliconate was 97 / 3. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 100 nm after drying, thereby producing a laminate.
[0125] [Example 2]
[0126] <Inorganic Compound Layer>
[0127] In the same manner as in Example 1, an inorganic compound layer was formed.
[0128] <Protection layer>
[0129] (Organic component solution)
[0130] A modified polyvinyl alcohol (hereinafter sometimes referred to as modified PVA, degree of polymerization 1,700, degree of saponification 93.0%) having a lactone structure and a carbonyl group-containing cyclic structure, which is a water-soluble resin, is added to a solvent having a mass ratio of water / isopropyl alcohol = 97 / 3, and heated and stirred at 90°C to obtain an organic component solution having a solid content of 12% by mass.
[0131] (Inorganic component solution)
[0132] In the same manner as in Example 1, a hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) and a hydrolyzed solution of pentameric silicate (hydrolyzed solution B) were obtained.
[0133] (Forming a protective layer)
[0134] The organic component solution, hydrolyzed solution A, and hydrolyzed solution B were mixed and stirred so that the modified PVA content was 20% by mass, the solid content of the urea-containing siliconate was 2.0%, and the SiO2-equivalent mass ratio of the linear polysiloxane to the siliconate was 97 / 3. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 100 nm after drying, thereby producing a laminate.
[0135] [Example 3]
[0136] <Inorganic Compound Layer>
[0137] In the same manner as in Example 1, an inorganic compound layer was formed.
[0138] <Protection layer>
[0139] (Organic component solution)
[0140] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0141] (Inorganic component solution)
[0142] In the same manner as in Example 1, a hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained.
[0143] Next, 7.0 g of 0.06 N aqueous hydrochloric acid solution was added dropwise to a solution of 11.2 g of ethyl silicate 48 (linear oligomer with an average decamer) manufactured by Colcoat Corporation as a linear polysiloxane and 16.9 g of methanol to obtain a decamer silicate hydrolyzed liquid (hydrolyzed liquid B).
[0144] (Forming a protective layer)
[0145] The organic component solution, hydrolyzed solution A, and hydrolyzed solution B were mixed and stirred to achieve a modified PVA content of 30% by mass, a solids content of a urea-containing siliconate of 3.2%, and a SiO2-equivalent mass ratio of 95 / 5 for the linear polysiloxane and siliconate, respectively. The mixture was then diluted with water to produce a coating solution having a solids content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 350 nm after drying, thereby producing a laminate.
[0146] [Example 4]
[0147] <Inorganic Compound Layer>
[0148] In the same manner as in Example 1, an inorganic compound layer was formed.
[0149] <Protection layer>
[0150] (Organic component solution)
[0151] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0152] (Inorganic component solution)
[0153] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0154] Next, 7.0 g of 0.06 N aqueous hydrochloric acid solution was added dropwise to a solution of 11.2 g of methyl silicate 51 (a linear oligomer having an average tetramer) manufactured by Colcoat Corporation as a linear polysiloxane and 16.9 g of methanol to obtain a tetrameric silicate hydrolyzed liquid (hydrolyzed liquid B).
[0155] Next, 18.6 g of a 0.02 N aqueous hydrochloric acid solution was added dropwise while stirring to a solution of 11.7 g of KBE-04 (tetraethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., which is a silicon alkoxide having no urea group, and 4.7 g of methanol to obtain a silicon alkoxide hydrolyzed solution having no urea group (hydrolyzed solution C).
[0156] (Forming a protective layer)
[0157] The organic component solution, hydrolysis solution A, hydrolysis solution B, and hydrolysis solution C were mixed and stirred so that the content of modified PVA was 30% by mass, the solid content of silicon alkoxide having a urea group was 3.2%, and the mass ratio of linear polysiloxane to total silicon alkoxide, calculated as SiO2, was 15 / 85. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 500 nm after drying, thereby producing a laminate.
[0158] [Example 5]
[0159] <Inorganic Compound Layer>
[0160] In the same manner as in Example 1, an inorganic compound layer was formed.
[0161] <Protection layer>
[0162] (Organic component solution)
[0163] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0164] (Inorganic component solution)
[0165] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0166] Next, 7.0 g of 0.06 N aqueous hydrochloric acid solution was added dropwise to a solution of 11.2 g of methyl silicate 53A (linear oligomer with an average heptamer) manufactured by COLCOAT Corporation as a linear polysiloxane and 16.9 g of methanol to obtain a heptamer silicate hydrolyzed liquid (hydrolyzed liquid B).
[0167] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0168] (Forming a protective layer)
[0169] The organic component solution, hydrolysis solution A, hydrolysis solution B, and hydrolysis solution C were mixed and stirred so that the content of modified PVA was 30% by mass, the solid content of silicon alkoxide having a urea group was 3.2%, and the mass ratio of linear polysiloxane to total silicon alkoxide, calculated as SiO2, was 15 / 85. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 500 nm after drying, thereby producing a laminate.
[0170] [Example 6]
[0171] <Inorganic Compound Layer>
[0172] In the same manner as in Example 1, an inorganic compound layer was formed.
[0173] <Protection layer>
[0174] (Organic component solution)
[0175] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0176] (Inorganic component solution)
[0177] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0178] Next, in the same manner as in Example 3, a decamer silicate hydrolyzed liquid (hydrolyzed liquid B) was obtained.
[0179] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0180] (Forming a protective layer)
[0181] The organic component solution, hydrolysis solution A, hydrolysis solution B, and hydrolysis solution C were mixed and stirred so that the modified PVA content was 50% by mass, the solid content of the silicon alkoxide having a urea group was 5.5%, and the mass ratio of the linear polysiloxane to the total silicon alkoxide, calculated as SiO2, was 50 / 50. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 250 nm after drying, thereby producing a laminate.
[0182] [Example 7]
[0183] <Inorganic Compound Layer>
[0184] In the same manner as in Example 1, an inorganic compound layer was formed.
[0185] <Protection layer>
[0186] (Organic component solution)
[0187] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0188] (Inorganic component solution)
[0189] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0190] Next, in the same manner as in Example 3, a decamer silicate hydrolyzed liquid (hydrolyzed liquid B) was obtained.
[0191] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0192] (Forming a protective layer)
[0193] The organic component solution, hydrolysis solution A, hydrolysis solution B, and hydrolysis solution C were mixed and stirred so that the modified PVA content was 30% by mass, the solid content of the silicon alkoxide having a urea group was 8.4%, and the mass ratio of the linear polysiloxane to the total silicon alkoxide, calculated as SiO2, was 60 / 40. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 250 nm after drying, thereby producing a laminate.
[0194] [Example 8]
[0195] <Inorganic Compound Layer>
[0196] In the same manner as in Example 1, an inorganic compound layer was formed.
[0197] <Protection layer>
[0198] (Organic component solution)
[0199] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0200] (Inorganic component solution)
[0201] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0202] Next, in the same manner as in Example 3, a decamer silicate hydrolyzed liquid (hydrolyzed liquid B) was obtained.
[0203] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0204] (Forming a protective layer)
[0205] The organic component solution, hydrolysis solution A, hydrolysis solution B, and hydrolysis solution C were mixed and stirred so that the content of modified PVA was 30% by mass, the solid content of silicon alkoxide having a urea group was 8.4%, and the mass ratio of linear polysiloxane to total silicon alkoxide, calculated as SiO2, was 40 / 60. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 250 nm after drying, thereby producing a laminate.
[0206] [Example 9]
[0207] <Inorganic Compound Layer>
[0208] In the same manner as in Example 1, an inorganic compound layer was formed.
[0209] <Protection layer>
[0210] (Organic component solution)
[0211] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0212] (Inorganic component solution)
[0213] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0214] Next, in the same manner as in Example 3, a decamer silicate hydrolyzed liquid (hydrolyzed liquid B) was obtained.
[0215] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0216] (Forming a protective layer)
[0217] The organic component solution, hydrolysis solution A, hydrolysis solution B, and hydrolysis solution C were mixed and stirred so that the content of modified PVA was 30% by mass, the solid content of silicon alkoxide having a urea group was 7.8%, and the mass ratio of linear polysiloxane to total silicon alkoxide, calculated as SiO2, was 40 / 60. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 250 nm after drying, thereby producing a laminate.
[0218] [Example 10]
[0219] <Inorganic Compound Layer>
[0220] In the same manner as in Example 1, an inorganic compound layer was formed.
[0221] <Protection layer>
[0222] (Organic component solution)
[0223] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0224] (Inorganic component solution)
[0225] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0226] Next, in the same manner as in Example 3, a decamer silicate hydrolyzed liquid (hydrolyzed liquid B) was obtained.
[0227] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0228] (Forming a protective layer)
[0229] The organic component solution, hydrolysis solution A, hydrolysis solution B, and hydrolysis solution C were mixed and stirred so that the content of modified PVA was 30% by mass, the solid content of silicon alkoxide having a urea group was 3.2%, and the mass ratio of linear polysiloxane to total silicon alkoxide, calculated as SiO2, was 40 / 60. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 250 nm after drying, thereby producing a laminate.
[0230] [Example 11]
[0231] <Inorganic Compound Layer>
[0232] A 12μm-thick biaxially oriented polyethylene terephthalate film ("Lumirror" (registered trademark) P60, manufactured by Toray Industries, Ltd.) was used as the substrate film. Aluminum was evaporated from the unwound substrate film using a high-frequency induction-heated crucible aluminum evaporation source in a roll-to-roll vacuum deposition machine, depositing aluminum onto the substrate film. Oxygen gas was supplied to the portion of the evaporated aluminum closest to the wound side of the substrate film, continuously forming an inorganic layer to a thickness of 40nm for the aluminum metal layer and 4nm for the aluminum oxide layer. The thicknesses of the aluminum metal layer and the aluminum oxide layer were measured using the following method.
[0233] First, X-ray photoelectron spectroscopy (XPS) is used to perform composition analysis and evaluation in the depth direction, and the inorganic film composition is confirmed by depth distribution. It should be noted that for metal elements, the components of the oxide component and the metal component are separated and distributed in a curve. While ion etching is performed from the surface layer of the resin layer and the protective layer side, data is collected until the substrate is reached, and the composition is confirmed to have a continuous increase or decrease based on the depth distribution of each element obtained. It should be noted that, with respect to whether there is a continuous increase or decrease, when the length of the increase or decrease is more than 2nm, it is judged to have a continuous increase or decrease.
[0234] The measurement conditions are as follows.
[0235] Equipment: X-ray photoelectron spectroscopy (Quantera SXM manufactured by PHI)
[0236] Excited X-rays: monochromatic AlKα 1,2 line (1486.6eV)
[0237] X-ray diameter: 100μm
[0238] Photoelectron escape angle 45° (inclination of the detector relative to the sample surface)
[0239] Ion etching conditions: Ar + Ion 3kV
[0240] Grating size 2×2mm (etching area)
[0241] Etching rate 12.0nm / min
[0242] Next, the total thickness of the inorganic layer was determined by the above method. The thickness of each of the aluminum metal layer and the aluminum oxide layer was calculated based on the total thickness of the inorganic layer and the region corresponding to the inorganic layer in the depth distribution.
[0243] <Protection layer>
[0244] (Organic component solution)
[0245] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0246] (Inorganic component solution)
[0247] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0248] Next, in the same manner as in Example 3, a decamer silicate hydrolyzed liquid (hydrolyzed liquid B) was obtained.
[0249] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0250] (Forming a protective layer)
[0251] The organic component solution, hydrolysis solution A, hydrolysis solution B, and hydrolysis solution C were mixed and stirred so that the content of modified PVA was 30% by mass, the solid content of silicon alkoxide having a urea group was 3.2%, and the mass ratio of linear polysiloxane to total silicon alkoxide, calculated as SiO2, was 40 / 60. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer having an average thickness of 250 nm after drying, thereby producing a laminate.
[0252] [Comparative Example 1]
[0253] Evaluation was conducted on a laminate provided with only the same inorganic compound layer as in Example 1 without providing a protective layer. However, the laminate showed poor gas barrier properties, gas barrier properties after retort treatment, and adhesion.
[0254] [Comparative Example 2]
[0255] <Inorganic Compound Layer>
[0256] In the same manner as in Example 1, an inorganic compound layer was formed.
[0257] <Protection layer>
[0258] (Organic component solution)
[0259] none.
[0260] (Inorganic component solution)
[0261] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0262] Next, in the same manner as in Example 3, a decamer silicate hydrolyzed liquid (hydrolyzed liquid B) was obtained.
[0263] (Forming a protective layer)
[0264] Without using a water-soluble resin, hydrolyzed solution A and hydrolyzed solution B were mixed and stirred to obtain a coating solution with a solid content of 12% by mass, such that the solid content of the silicon alkoxide having a urea group was 2.0% and the SiO2-converted mass ratio of the linear polysiloxane to the silicon alkoxide was 98 / 2. This solution was then diluted with water. This coating solution was applied to the inorganic compound layer and dried at 150°C to form a protective layer containing no water-soluble resin and having an average thickness of 350 nm after drying. This laminate was produced, but cracks in the protective layer prevented evaluation.
[0265] [Comparative Example 3]
[0266] <Inorganic Compound Layer>
[0267] In the same manner as in Example 1, an inorganic compound layer was formed.
[0268] <Protection layer>
[0269] (Organic component solution)
[0270] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0271] (Inorganic component solution)
[0272] A hydrolyzed solution of silicon alkoxide having a urea group (hydrolyzed solution A) was obtained in the same manner as in Example 1.
[0273] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0274] (Forming a protective layer)
[0275] The modified PVA content was 30% by mass, the solid content of urea-containing siliconates was 3.2%, and no linear polysiloxane was used. The organic component solution, hydrolyzed solutions A and B were mixed and stirred, and then diluted with water to produce a coating solution with a solid content of 12% by mass. This coating solution was applied to the inorganic compound layer and dried at 150°C to form a protective layer containing no linear polysiloxane (the SiO2-converted mass ratio of linear polysiloxane to total siliconates was 0 / 100) with an average thickness of 350 nm after drying, thereby producing a laminate. Due to the lack of linear polysiloxane, the laminate of this technical solution exhibited poor gas barrier properties and adhesion after retorting.
[0276] [Comparative Example 4]
[0277] <Inorganic Compound Layer>
[0278] In the same manner as in Example 1, an inorganic compound layer was formed.
[0279] <Protection layer>
[0280] (Organic component solution)
[0281] In the same manner as in Example 2, an organic component solution of modified PVA was obtained.
[0282] (Inorganic component solution)
[0283] In the same manner as in Example 3, a decamer silicate hydrolyzed liquid (hydrolyzed liquid B) was obtained.
[0284] Next, in the same manner as in Example 4, a hydrolyzed solution of silicon alkoxide having no urea group (hydrolyzed solution C) was obtained.
[0285] (Forming a protective layer)
[0286] Hydrolyzed solutions B and C were mixed and stirred to obtain a modified PVA content of 30% by mass, no urea-containing siliconate was used, and the SiO2-converted mass ratio of the linear polysiloxane to the siliconate (tetraethoxysilane alone) was 40 / 60. The mixture was then diluted with water to obtain a coating solution having a solid content of 12% by mass. This coating solution was applied onto the inorganic compound layer and dried at 150°C to form a protective layer containing no urea-containing siliconate having an average thickness of 350 nm after drying. This laminate was produced, but the adhesion was poor.
[0287] Regarding each of the above-mentioned Examples and Comparative Examples, Table 1 shows the composition of the laminated body, and Table 2 shows the characteristics of the laminated body.
[0288] [Table 1]
[0289]
[0290] [Table 2]
[0291] [Table 2]
[0292]
[0293] From the results of the above examples, it is understood that the laminate of the present invention exhibits excellent adhesion while exhibiting gas barrier properties.
[0294] Compared with the case where no protective layer is provided (Comparative Example 1) or the case where a protective layer is provided but a certain component is missing (Comparative Examples 2 to 4), by including a water-soluble polymer, a linear polysiloxane, and a silicon alkoxide having a urea group in the protective layer (Example 1), the adhesion and gas barrier properties after the steaming treatment are improved.
[0295] In addition, compared with Example 1, the gas barrier properties were improved by using a vinyl polymer having a carbonyl group in its cyclic structure as the water-soluble resin in the protective layer (Example 2). Furthermore, by setting the solid content ratio of the silicon alkoxide having a urea group to 2.5% or more relative to the total solid content of the protective layer, not only the gas barrier properties but also the adhesion were improved (Example 3).
[0296] By including a silicon alkoxide without urea groups in the protective layer, or by varying the type of linear polysiloxane used (tetramer, heptamer), or the average thickness of the protective layer, adhesion and post-retorting gas barrier properties were improved (Examples 4 and 5). Furthermore, by varying the solid content ratio of the silicon alkoxide with urea groups and the SiO₂-equivalent mass ratio of the linear polysiloxane to the total silicon alkoxide in the protective layer (Examples 6-10), adhesion, gas barrier properties, and post-retorting resistance (adhesion, gas barrier properties) were improved, while also enabling adjustment of various physical properties. Furthermore, even when the type of inorganic compound layer was varied, the protective layer's effects were consistently demonstrated (Example 11).
[0297] On the other hand, when no protective layer was provided (Comparative Example 1), adhesion and gas barrier properties deteriorated. When a protective layer was provided but no water-soluble resin was included (Comparative Example 2), cracks occurred on the side where the layers were stacked, making evaluation impossible. Furthermore, when the protective layer did not contain a linear polysiloxane (Comparative Example 3) or a silicon alkoxide containing a urea group (Comparative Example 4), even when a silicon alkoxide containing no urea group was included, either gas barrier properties or adhesion deteriorated.
Claims
1. A laminate comprising an inorganic compound layer and a protective layer laminated on at least one side of a substrate film, characterized in that: The protective layer contains at least a water-soluble polymer, a linear polysiloxane and a silicon alkoxide having a urea group.
2. The laminate according to claim 1, characterized in that The solid content ratio of the silicon alkoxide having a urea group is 2.5% by mass or more relative to the total solid content of the protective layer.
3. The laminate according to claim 1 or 2, characterized in that: The protective layer further includes silicon alkoxide having no urea group, and the mass ratio of the linear polysiloxane and the total silicon alkoxide contained in the protective layer calculated as SiO2 is in the range of linear polysiloxane / total silicon alkoxide=15 / 85 to 90 / 10.
4. The laminate according to claim 1 or 2, characterized in that: The water-soluble polymer contained in the protective layer is a vinyl polymer having a carbonyl group in a ring structure.
5. The laminate according to claim 1 or 2, characterized in that: The average thickness of the protective layer is 100-1000 nm.
6. The laminate according to claim 1 or 2, characterized in that: The inorganic compound layer includes aluminum oxide. 7 . A printed ink laminate, wherein a printing ink is laminated on the protective layer side of the laminate according to claim 1 or 2 .
8. A packaging body comprising the printed ink laminate according to claim 7. 9 . A packaging body comprising the laminate according to claim 1 or 2 and the printing ink laminate according to claim 7 .
Citation Information
Patent Citations
Solid-state color image sensor
JP1982039684A
Gas barrier film
JP2010131756A
Laminate and method of manufacturing the same
JP2012210744A
Barrier film and packaging material
JP2019209645A
Resin composition, and printed wiring board, laminated sheet, and prepreg using same
CN105504809A